Sunscreen and antibacterial layered composite fabric, preparation method and mask
By introducing quaternized zinc oxide/montmorillonite composite materials and functional modifiers into composite fabrics, the problem of lack of air filtration effect in existing fabrics is solved, and the excellent antibacterial, ultraviolet and filtration performance of the fabric is achieved. It is suitable for In the preparation of high-performance masks.
Patent Information
- Application Number
- CN202411389668.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The prior art composite fabrics perform well in antibacterial and UV protection, but lack air filtration, which limits their application.
The meltblown layer material is formed by preparing a quaternized zinc oxide/montmorillonite composite with antibacterial properties and mixing it with polypropylene meltblown resin. At the same time, by surface modification of polyester/cotton fabric, alkenylhein, allyl-β-cyclodextrin and 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl Functional components such as ]phenyl]-2H-benzotriazole have excellent antibacterial, ultraviolet and filtration properties.
It achieves excellent antibacterial and UV resistance of the fabric, and improves its air filtration performance, making it suitable for the preparation of high-performance masks.
Smart Images

Figure CN118906566B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of layered composite materials, and in particular to a sun-proof and antibacterial layered composite fabric, a preparation method and a mask. Background Art
[0002] Textiles provide breeding grounds for bacteria due to their microporous structure and large surface area. Antibacterial modification of textiles can protect them from bacterial erosion during use and extend their service life. At the same time, the UV shielding rate of general fiber fabrics is low, and further processing is required to block UV rays through reflection, absorption, etc. to achieve better sun protection effect; masks are functional fabrics with filtering and protective properties, and their functional properties such as antibacterial and anti-ultraviolet properties are gradually expanding. Therefore, it is necessary to develop the functional fabrics for masks to meet the needs of multi-functional development.
[0003] Existing technologies such as Chinese patent CN109291563A disclose an antibacterial, health-care, UV-resistant environmentally friendly composite fabric and its preparation method, which separately prepares an outer layer fabric with antibacterial and UV-resistant properties, a thin and breathable interlayer fabric, and a skin-friendly and antibacterial inner layer fabric, and the composite fabric obtained after compounding has antibacterial and UV-resistant effects. Although the prepared composite fabric has good antibacterial and UV-resistant properties, it is limited in application due to the lack of air filtration effect. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sunscreen and antibacterial layered composite fabric and a preparation method. The fabric has excellent UV resistance and antibacterial properties, good filtering performance, and can be used to prepare masks.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a sun-proof and antibacterial layered composite fabric comprises the following steps:
[0007] Step 1, preparing meltblown layer material;
[0008] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material and the dicumyl peroxide are mixed and melt-reacted to obtain an antibacterial polypropylene melt after the reaction is completed. The antibacterial polypropylene melt is melt-spun by a melt-blown spinning machine to obtain a melt-blown layer material.
[0009] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0010] Step (1), mixing montmorillonite, hexadecyltrimethylammonium bromide and water, reacting, adding a regulator to adjust the pH value after the reaction, adding zinc acetate and tetraethoxysilane, and continuing the reaction, and after the reaction, centrifuging, filtering, washing, drying, grinding and sieving, and calcining to obtain a zinc oxide / montmorillonite composite material;
[0011] Step (2), ultrasonically dispersing the zinc oxide / montmorillonite composite material and toluene, adding water, and dropwise adding 3-chloropropyltrimethoxysilane. After the dropwise addition is completed, reacting, filtering, washing, and drying after the reaction is completed to obtain a modified zinc oxide / montmorillonite composite material;
[0012] The dimethylaminoethyl methacrylate is mixed with ethanol and isopropanol to dissolve, and the modified zinc oxide / montmorillonite composite material and potassium iodide are added to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a quaternized zinc oxide / montmorillonite composite material.
[0013] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0014] Step (1), mixing polyester fiber with sodium hydroxide aqueous solution, pre-treating, taking out after treatment, washing to neutrality, and drying to obtain pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, spinning cotton fiber into yarn as weft yarn, weaving to obtain polyester / cotton fabric;
[0015] Step (2), mixing γ-methacryloxypropyltrimethoxysilane, ethanol aqueous solution, and pretreated polyester / cotton fabric, reacting, taking out after the reaction, washing, continuing the reaction, and drying after the reaction to obtain olefin-based polyester / cotton fabric;
[0016] The modified polyester / cotton fabric is prepared by mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate and water, and then impregnating the mixture. After the impregnation, the mixture is baked to obtain the modified polyester / cotton fabric.
[0017] Wherein, alkenyl hydantoin is prepared by the following steps:
[0018] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride and water are mixed and dissolved, and reacted. After the reaction is completed, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione is added and the reaction is continued. After the reaction is completed, the solvent water is removed by rotary evaporation to obtain a reaction product, ethanol is added, stirred, filtered, and dried to obtain modified hydantoin;
[0019] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol are mixed and reacted. After the reaction is completed, the solvent water and ethanol are removed by rotary evaporation, and the mixture is dried to obtain alkenyl hydantoin;
[0020] Step (3), immersing the modified polyester / cotton fabric in a sodium hypochlorite aqueous solution for chlorination, taking it out after the chlorination is completed, washing it with water, and drying it to obtain a surface layer fabric and an inner layer fabric respectively;
[0021] Step 3: Compound the surface layer fabric, melt-blown layer material and inner layer fabric in sequence to obtain a sun-proof and antibacterial layered composite fabric.
[0022] Preferably, in the step 1, the mass ratio of polypropylene melt-blown resin, quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide is 100:3-5:0.4-0.5; the melting reaction conditions are: in a twin-screw extruder, the screw speed is 250-300r / min, and the melting reaction is carried out at a temperature of 230-250°C for 8-10min; the gram weight of the melt-blown layer material is 20-30g / m 2 .
[0023] Preferably, in the step 1, the operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 240-260°C, the melt pump speed is 200-220r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 20-24cm and a temperature of 5-10°C, and then charged for 1-2min at a voltage of 45-50kV and a spacing of 30-35cm.
[0024] Preferably, when preparing the quaternized zinc oxide / montmorillonite composite material in step (1), the mass ratio of montmorillonite, hexadecyltrimethylammonium bromide, water, zinc acetate and tetraethoxysilane is 1:4-4.2:40-50:1.8-2:1.6-1.8; the reaction conditions are: reacting at a temperature of 70-80°C for 12-16h; continuing the reaction conditions are: continuing the reaction at a pH value of 8-9 and a temperature of 70-80°C for 2-3h; and the calcination conditions are: calcining at a temperature of 550-580°C for 5-6h.
[0025] Preferably, the modifier comprises triethanolamine.
[0026] Furthermore, the sieve mesh number is 500 meshes.
[0027] Preferably, when preparing the quaternized zinc oxide / montmorillonite composite material in step 1, in step (2), the mass ratio of the zinc oxide / montmorillonite composite material, 3-chloropropyltrimethoxysilane, toluene and water is 5:5.5-6:40-50:5-6, and the dripping time of 3-chloropropyltrimethoxysilane is 10-15 min; when preparing the modified zinc oxide / montmorillonite composite material, the reaction conditions are: reacting at room temperature for 8-10 h; the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide is 4.7-5:10-15:20-30:5:0.2-0.3; when preparing the quaternized zinc oxide / montmorillonite composite material, the reaction conditions are: reacting at a temperature of 50-60°C for 8-10 h.
[0028] Preferably, in step (1) of step 2: the mass ratio of polyester fiber to sodium hydroxide aqueous solution is 1:40-50, and the sodium hydroxide aqueous solution is 150 g / L sodium hydroxide aqueous solution; the pretreatment conditions are: pretreatment at 70-80°C for 20-30 min; the yarn count of the pretreated polyester fiber is 30-40S in British standard; the yarn count of the cotton fiber is 30-40S in British standard; the weight of the polyester / cotton fabric is 120-130 g / m 2 .
[0029] Preferably, in step (2) of step 2: the mass ratio of γ-methacryloxypropyltrimethoxysilane, 80wt% ethanol aqueous solution, and pretreated polyester / cotton fabric is 5-6:100:2, and the ethanol aqueous solution is 80wt% ethanol aqueous solution; the reaction conditions are: reacting at a temperature of 30-40°C for 3-4h; and the continued reaction conditions are: continuing the reaction at a temperature of 100-120°C in a drying oven for 1-2h.
[0030] Preferably, in step (2) of step 2: the mass ratio of alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate, and water is 20:4-5:1.8-2:2-3:0.8-1:1000; the dipping operation includes: dipping at a temperature of 75-85°C for 0.5-1h, double dipping and double rolling, and the rolling rate is 78-82%.
[0031] Preferably, in step (2) of step 2, when preparing alkenyl hydantoin, the mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione is 8.7-9:5.8-6:9.6-10:150-180:8.2-8.5; when preparing modified hydantoin, the reaction conditions are: react at 40-50°C for 20-40 minutes, and the continued reaction conditions are: continue to react at 40-50°C for 24-26 hours; the mass ratio of 4-allyloxybenzaldehyde, modified hydantoin, water, and ethanol is 34-35:16.5-17:40-50:60-70; when preparing alkenyl hydantoin, the reaction conditions are: react at 60-70°C for 18-22 hours.
[0032] Preferably, in step (3) of step 2: the bath ratio of the modified polyester / cotton fabric to the sodium hypochlorite aqueous solution is 40-50:1, the sodium hypochlorite aqueous solution is a 10wt% sodium hypochlorite aqueous solution; and the chlorination conditions are: chlorination at room temperature for 1-2h.
[0033] Preferably, a sun-proof and antibacterial layered composite fabric is prepared by the method for preparing the sun-proof and antibacterial layered composite fabric as described above.
[0034] Preferably, a mask is prepared using the sun-proof and antibacterial layered composite fabric as described above.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The invention prepares a quaternary ammonium zinc oxide / montmorillonite composite material with antibacterial property, adds the composite material into a polypropylene melt-blown resin for melting reaction, and prepares a melt-blown layer material; grafts a silane coupling agent containing a carbon-carbon double bond functional group onto the surface of a polyester / cotton fiber, and rolls the fiber with a finishing solution containing alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole and an initiator; and the obtained modified polyester / cotton fabric is chlorinated, so that the obtained surface layer fabric and inner layer fabric have both antibacterial property and anti-ultraviolet ability, and the moisture absorption property is improved; and the surface layer fabric, the melt-blown layer material and the inner layer fabric are compounded in sequence, so that the obtained multi-layer composite fabric has excellent anti-ultraviolet and antibacterial properties, good filtering property, and can be used as a raw material to prepare a mask.
[0037] The polypropylene (PP) melt-blown nonwoven fabric is a three-dimensional structure formed by randomly arranging polypropylene fibers with a micron diameter, has a large specific surface area and multi-directional curved pores, can better adsorb, intercept and block particulate matter, and plays a role in filtering air; the present invention introduces hexadecyl ammonium bromide into the interlayer of montmorillonite through cation exchange, adds precursors tetraethoxysilane and zinc acetate, induces silicon dioxide and zinc oxide to grow together on the montmorillonite carrier through high temperature, alleviates the tendency of zinc oxide agglomeration, and obtains a zinc oxide / montmorillonite composite material with antibacterial and anti-ultraviolet properties, further surface-modifies the surface of the nonwoven fabric by grafting 3-chloropropyltrimethoxysilane, and then reacts with dimethylaminoethyl methacrylate to undergo quaternization reaction to further improve the antibacterial property, and at the same time introduces an active group carbon-carbon double bond, and the obtained quaternized zinc oxide / montmorillonite composite material can be grafted on the polypropylene molecular chain under the condition of an initiator, improves the compatibility between the filler and the matrix, and the obtained melt-blown layer material not only has good anti-ultraviolet and filtering properties, but also has excellent antibacterial properties;
[0038] The invention spins polyester fibers and cotton fibers that have been treated with alkali into yarns, weaves them to obtain polyester / cotton fabrics, grafts the polyester / cotton fabrics with a silane coupling agent containing a carbon-carbon double bond functional group to obtain alkenyl polyester / cotton fabrics, and rolls the fabrics with a finishing solution containing alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole and an initiator, so that each functional component is grafted and fixed on the surface of the polyester / cotton fabric through a free radical reaction, chlorinates the obtained modified polyester / cotton fabrics to obtain a surface fabric and an inner fabric, and composites the surface fabric, the melt-blown layer material and the inner fabric to obtain a sunscreen and antibacterial layered composite fabric;
[0039] Among them, alkenyl hydantoin is prepared by an amidation reaction between 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione and L-arginine with antibacterial properties, followed by a Schiff base reaction with 4-allyloxybenzaldehyde. As a precursor structure of halamine antibacterial agents, it forms a nitrogen-halogen bond after chlorination, and has many advantages such as broad-spectrum bactericidal properties, stability, regeneration of antibacterial properties and safety. It can synergize with L-arginine with antibacterial properties and Schiff base bonds to effectively improve the antibacterial properties of fabrics. Cyclodextrin and its derivatives have a special molecular structure with hydrophilicity on the outside and hydrophobicity on the inside. Fixing them on the fabric can, on the one hand, further improve the air filtration efficiency of the fabric, and on the other hand, improve the hygroscopicity of the fabric. 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, as a benzotriazole ultraviolet absorption monomer, can improve the anti-ultraviolet properties of the fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1It is a process flow chart for preparing a sun-proof and antibacterial layered composite fabric and a sun-proof and antibacterial mask in the present invention;
[0041] Figure 2 It is a schematic structural diagram of the sun-proof and antibacterial layered composite fabric prepared in the present invention;
[0042] Figure 3 It is a bar graph of the antibacterial rates of Examples 1-5 and Comparative Examples 1-2 in the performance test of the present invention;
[0043] Figure 4 It is a bar graph of UPF values of samples 1-7 in the performance test of the present invention;
[0044] In the figure:
[0045] 1. Surface fabric; 2. Meltblown layer material; 3. Inner layer fabric. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] This embodiment discloses a method for preparing a sun-proof and antibacterial layered composite fabric, comprising the following steps:
[0049] Step 1, preparing meltblown layer material;
[0050] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide were mixed in a mass ratio of 100:3:0.4, and melt-reacted for 10 minutes in a twin-screw extruder at a screw speed of 250 r / min and a temperature of 230°C. After the reaction, an antibacterial polypropylene melt was obtained, and the antibacterial polypropylene melt was melt-spun by a melt-blown spinning machine to obtain a 20 g / m 2 Meltblown layer material;
[0051] The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 240°C, the melt pump speed is 200r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 20cm and a temperature of 5°C, and then charged for 2min at a voltage of 45kV and a spacing of 30cm;
[0052] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0053] Step (1), mixing montmorillonite, hexadecyltrimethylammonium bromide and water, reacting at 75°C for 14 hours, adding triethanolamine to adjust the pH value to 8.5, adding zinc acetate and tetraethoxysilane, and continuing to react at 75°C for 2.5 hours, centrifuging and filtering after the reaction, taking the filter cake, washing it with water 7 times the mass of the filter cake, drying it at 75°C for 22 hours, grinding it through a 500-mesh sieve after drying, and calcining it at 560°C for 5.5 hours to obtain a zinc oxide / montmorillonite composite material;
[0054] The mass ratio of montmorillonite, hexadecyltrimethylammonium bromide, water, zinc acetate and tetraethoxysilane is 1:4.1:45:1.9:1.7;
[0055] Step (2), ultrasonically dispersing the zinc oxide / montmorillonite composite material and toluene for 15 minutes, adding water, and dripping 3-chloropropyltrimethoxysilane for 12 minutes, wherein the mass ratio of the zinc oxide / montmorillonite composite material, 3-chloropropyltrimethoxysilane, toluene and water is 5:5.8:45:5.5. After the dripping is completed, reacting at room temperature for 9 hours. After the reaction is completed, filtering, taking the filter cake, adding toluene 6 times the mass of the filter cake for washing, and drying at 55° C. for 16 hours to obtain a modified zinc oxide / montmorillonite composite material;
[0056] Mix dimethylaminoethyl methacrylate with ethanol and isopropanol to dissolve, add modified zinc oxide / montmorillonite composite material and potassium iodide, the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide is 4.7:10:20:5:0.2, react at 50°C for 10h, filter after the reaction, take the filter cake, add ethanol 5 times the mass of the filter cake to wash, and dry at 50°C for 24h to obtain a quaternary ammonium zinc oxide / montmorillonite composite material;
[0057] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0058] Step (1), mixing the polyester fiber with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:40, pre-treating at 70° C. for 30 min, taking out after the treatment, adding water to wash until neutral, and drying at 50° C. for 20 h to obtain the pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, the yarn count is 30S in British standard, spinning cotton fiber into yarn as weft yarn, the yarn count is 30S in British standard, weaving, and obtaining a yarn with a gram weight of 120 g / m 2 Polyester / cotton fabric;
[0059] Step (2), mixing γ-methacryloxypropyltrimethoxysilane, 80wt% ethanol aqueous solution, and pretreated polyester / cotton fabric in a mass ratio of 5.5:100:2, reacting at 35°C for 3.5h, taking out after the reaction, adding 6 times the mass of ethanol of the pretreated polyester / cotton fabric for washing, and continuing to react at 110°C in a drying oven for 1.5h. After the reaction, drying at 75°C for 11h to obtain olefin-based polyester / cotton fabric;
[0060] The modified polyester / cotton fabric is prepared by mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate and water in a mass ratio of 20:4:1.8:2:0.8:1000, dipping at 75°C for 1 hour, double dipping and double rolling with a rolling rate of 78%, and baking at 150°C for 3 minutes after the dipping to obtain the modified polyester / cotton fabric;
[0061] Wherein, alkenyl hydantoin is prepared by the following steps:
[0062] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, and water were mixed and dissolved, and reacted at 40°C for 40 minutes. After the reaction, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was added. The mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was 8.7:5.8:9.6:150:8.2. The reaction was continued at 40°C for 26 hours. After the reaction was completed, the solvent water was removed by rotary evaporation at 70°C to obtain a reaction product. Ethanol 4 times the mass of the reaction product was added, stirred for 0.5 hours, filtered, and the filter cake was taken and dried at 70°C for 16 hours to obtain modified hydantoin.
[0063] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol were mixed in a mass ratio of 34:16.5:40:60, reacted at 60°C for 22h, and after the reaction, the solvent water and ethanol were removed by rotary evaporation at 70°C, and dried at 50°C for 14h to obtain allylated hydantoin;
[0064] Step (3), immersing the modified polyester / cotton fabric in a 10wt% sodium hypochlorite aqueous solution with a bath ratio of 40:1, chlorinating at room temperature for 1 hour, taking out after the chlorination, washing with water, and drying at 40°C for 12 hours to obtain a surface layer fabric and an inner layer fabric, respectively;
[0065] Step 3: laminate the surface fabric, meltblown layer material, and inner layer fabric in turn, align the layers, use polyester filament sewing thread as sewing thread, and sew the surface fabric, meltblown layer material, and inner layer fabric through a multi-layer fabric quilting machine to obtain a sun-proof and antibacterial layered composite fabric.
[0066] Example 2
[0067] This embodiment discloses a method for preparing a sun-proof and antibacterial layered composite fabric, comprising the following steps:
[0068] Step 1, preparing meltblown layer material;
[0069] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide were mixed in a mass ratio of 100:3.5:0.4, and melt-reacted in a twin-screw extruder at a screw speed of 260 r / min and a temperature of 235°C for 9 minutes. After the reaction, an antibacterial polypropylene melt was obtained. The antibacterial polypropylene melt was melt-spun by a melt-blown spinning machine to obtain a 22 g / m 2 Meltblown layer material;
[0070] The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 245°C, the melt pump speed is 210r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 22cm and a temperature of 8°C, and then charged for 2min at a voltage of 45kV and a spacing of 33cm;
[0071] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0072] Dimethylaminoethyl methacrylate was mixed and dissolved with ethanol and isopropanol, and a modified zinc oxide / montmorillonite composite material and potassium iodide were added, wherein the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide was 4.8:12:25:5:0.25. The preparation of the modified zinc oxide / montmorillonite composite material was the same as that in Example 1, and the reaction was carried out at a temperature of 55° C. for 9 hours. After the reaction was completed, the filter cake was filtered, and ethanol 5 times the mass of the filter cake was added for washing, and the filter cake was dried at a temperature of 55° C. for 22 hours to obtain a quaternary ammonium zinc oxide / montmorillonite composite material.
[0073] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0074] Step (1), mixing the polyester fiber with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:45, pre-treating at 75° C. for 25 min, taking out after the treatment, adding water to wash until neutral, and drying at 55° C. for 20 h to obtain the pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, the yarn count is 32S in British standard, spinning cotton fiber into yarn as weft yarn, the yarn count is 32S in British standard, weaving, and obtaining a weight of 123 g / m 2 Polyester / cotton fabric;
[0075] Step (2), mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate, and water in a mass ratio of 20:4.3:1.85:2.3:0.85:1000, the preparation of alkenyl polyester / cotton fabric is the same as that in Example 1, dipping at 80°C for 0.8h, double dipping and double rolling, with a rolling rate of 79%, and after the dipping is completed, baking at 150°C for 2.5min to obtain a modified polyester / cotton fabric;
[0076] Wherein, alkenyl hydantoin is prepared by the following steps:
[0077] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, and water were mixed and dissolved, and reacted at 45°C for 30 minutes. After the reaction, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was added. The mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was 8.8:5.85:9.7:160:8.3. The reaction was continued at 45°C for 25 hours. After the reaction was completed, the solvent water was removed by rotary evaporation at 75°C to obtain a reaction product. Ethanol 4 times the mass of the reaction product was added, stirred for 1 hour, filtered, and the filter cake was taken and dried at 75°C for 14 hours to obtain modified hydantoin.
[0078] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol were mixed in a mass ratio of 34.3:16.6:45:65, reacted at 65°C for 20 hours, and after the reaction, the solvent water and ethanol were removed by rotary evaporation at 70°C, and dried at 55°C for 13 hours to obtain allylated hydantoin;
[0079] Step (3), immersing the modified polyester / cotton fabric in a 10wt% sodium hypochlorite aqueous solution with a bath ratio of 45:1, chlorinating at room temperature for 1.5h, taking out after the chlorination, washing with water, and drying at 45°C for 11h to obtain a surface layer fabric and an inner layer fabric respectively;
[0080] Step 3: laminate the surface fabric, meltblown layer material, and inner layer fabric in turn, align the layers, use polyester filament sewing thread as sewing thread, and sew the surface fabric, meltblown layer material, and inner layer fabric through a multi-layer fabric quilting machine to obtain a sun-proof and antibacterial layered composite fabric.
[0081] Example 3
[0082] This embodiment discloses a method for preparing a sun-proof and antibacterial layered composite fabric, comprising the following steps:
[0083] Step 1, preparing meltblown layer material;
[0084] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide were mixed in a mass ratio of 100:4:0.45, and melt-reacted in a twin-screw extruder at a screw speed of 280 r / min and a temperature of 240°C for 9 minutes. After the reaction, an antibacterial polypropylene melt was obtained, and the antibacterial polypropylene melt was melt-spun by a melt-blown spinning machine to obtain a 25 g / m 2 Meltblown layer material;
[0085] The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 250°C, the melt pump speed is 210r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 22cm and a temperature of 8°C, and then charged for 1.5min at a voltage of 48kV and a spacing of 33cm;
[0086] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0087] Dimethylaminoethyl methacrylate was mixed and dissolved with ethanol and isopropanol, and a modified zinc oxide / montmorillonite composite material and potassium iodide were added, wherein the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide was 4.85:13:25:5:0.25. The preparation of the modified zinc oxide / montmorillonite composite material was the same as that in Example 1, and the reaction was carried out at a temperature of 55° C. for 9 hours. After the reaction was completed, the filter cake was taken, and ethanol 6 times the mass of the filter cake was added for washing, and the mixture was dried at a temperature of 55° C. for 22 hours to obtain a quaternary ammonium zinc oxide / montmorillonite composite material.
[0088] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0089] Step (1), mixing the polyester fiber with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:45, pre-treating at 75° C. for 25 min, taking out after the treatment, adding water to wash until neutral, and drying at 55° C. for 19 h to obtain the pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, the yarn count is 35S in British standard, spinning cotton fiber into yarn as weft yarn, the yarn count is 35S in British standard, weaving, and obtaining a yarn with a gram weight of 125 g / m 2 Polyester / cotton fabric;
[0090] Step (2), mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate, and water in a mass ratio of 20:4.5:1.9:2.5:0.9:1000, the preparation of the alkenyl polyester / cotton fabric is the same as that in Example 1, dipping at 80°C for 0.8h, double dipping and double rolling, with a rolling rate of 80%, and after the dipping is completed, baking at 155°C for 2.5min to obtain a modified polyester / cotton fabric;
[0091] Wherein, alkenyl hydantoin is prepared by the following steps:
[0092] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, and water were mixed and dissolved, and reacted at 45°C for 30 minutes. After the reaction, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was added. The mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was 8.85:5.9:9.8:170:8.35. The reaction was continued at 45°C for 25 hours. After the reaction was completed, the solvent water was removed by rotary evaporation at 75°C to obtain a reaction product. Ethanol 4.5 times the mass of the reaction product was added, stirred for 0.8 hours, filtered, and the filter cake was taken and dried at 75°C for 14 hours to obtain modified hydantoin.
[0093] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol were mixed in a mass ratio of 34.5:16.8:45:65, reacted at 65°C for 20h, after the reaction, the solvent water and ethanol were removed by rotary evaporation at 70°C, and dried at 55°C for 13h to obtain allylated hydantoin;
[0094] Step (3), immersing the modified polyester / cotton fabric in a 10wt% sodium hypochlorite aqueous solution with a bath ratio of 45:1, chlorinating at room temperature for 1.5h, taking out after the chlorination, washing with water, and drying at 45°C for 11h to obtain a surface layer fabric and an inner layer fabric respectively;
[0095] Step 3: laminate the surface fabric, meltblown layer material, and inner layer fabric in turn, align the layers, use polyester filament sewing thread as sewing thread, and sew the surface fabric, meltblown layer material, and inner layer fabric through a multi-layer fabric quilting machine to obtain a sun-proof and antibacterial layered composite fabric.
[0096] Example 4
[0097] This embodiment discloses a method for preparing a sun-proof and antibacterial layered composite fabric, comprising the following steps:
[0098] Step 1, preparing meltblown layer material;
[0099] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide were mixed in a mass ratio of 100:4.5:0.45, and melt-reacted in a twin-screw extruder at a screw speed of 290 r / min and a temperature of 250°C for 9 minutes. After the reaction, an antibacterial polypropylene melt was obtained. The antibacterial polypropylene melt was melt-spun by a melt-blown spinning machine to obtain a 28 g / m 2 Meltblown layer material;
[0100] The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 255°C, the melt pump speed is 210r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 22cm and a temperature of 8°C, and then charged for 1min at a voltage of 50kV and a spacing of 33cm.
[0101] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0102] Dimethylaminoethyl methacrylate was mixed and dissolved with ethanol and isopropanol, and a modified zinc oxide / montmorillonite composite material and potassium iodide were added, wherein the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide was 4.9:14:25:5:0.25. The preparation of the modified zinc oxide / montmorillonite composite material was the same as that in Example 1, and the reaction was carried out at 60° C. for 9 h. After the reaction was completed, the mixture was filtered, and the filter cake was taken, and ethanol 6 times the mass of the filter cake was added for washing, and the mixture was dried at 55° C. for 22 h to obtain a quaternary ammonium zinc oxide / montmorillonite composite material.
[0103] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0104] Step (1), mixing the polyester fiber with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:45, pre-treating at 80° C. for 25 min, taking out after the treatment, adding water to wash until neutral, and drying at 60° C. for 18 h to obtain the pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, the yarn count is British count 38S, spinning cotton fiber into yarn as weft yarn, the yarn count is British count 38S, weaving, and obtaining a gram weight of 128 g / m 2 Polyester / cotton fabric;
[0105] Step (2), mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate, and water in a mass ratio of 20:4.8:1.9:2.8:0.95:1000, the preparation of the alkenyl polyester / cotton fabric is the same as that in Example 1, dipping at 80°C for 1h, double dipping and double rolling, with a rolling rate of 81%, and after the dipping is completed, baking at 155°C for 2min to obtain a modified polyester / cotton fabric;
[0106] Wherein, alkenyl hydantoin is prepared by the following steps:
[0107] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, and water were mixed and dissolved, and reacted at 45°C for 30 minutes. After the reaction, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was added. The mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was 8.9:5.95:9.9:170:8.4. The reaction was continued at 45°C for 25 hours. After the reaction was completed, the solvent water was removed by rotary evaporation at 75°C to obtain a reaction product. Ethanol 5 times the mass of the reaction product was added, stirred for 0.5 hours, filtered, and the filter cake was taken and dried at 75°C for 14 hours to obtain modified hydantoin.
[0108] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol were mixed in a mass ratio of 34.8:16.9:45:65, reacted at 65°C for 20 hours, and after the reaction, the solvent water and ethanol were removed by rotary evaporation at 70°C, and dried at 60°C for 13 hours to obtain allylated hydantoin;
[0109] Step (3), immersing the modified polyester / cotton fabric in a 10wt% sodium hypochlorite aqueous solution with a bath ratio of 50:1, chlorinating at room temperature for 1 hour, taking out after the chlorination, washing with water, and drying at 45°C for 11 hours to obtain a surface layer fabric and an inner layer fabric, respectively;
[0110] Step 3: laminate the surface fabric, meltblown layer material, and inner layer fabric in turn, align the layers, use polyester filament sewing thread as sewing thread, and sew the surface fabric, meltblown layer material, and inner layer fabric through a multi-layer fabric quilting machine to obtain a sun-proof and antibacterial layered composite fabric.
[0111] Example 5
[0112] This embodiment discloses a method for preparing a sun-proof and antibacterial layered composite fabric, comprising the following steps:
[0113] Step 1, preparing meltblown layer material;
[0114] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide were mixed in a mass ratio of 100:5:0.5, and melt-reacted in a twin-screw extruder at a screw speed of 300 r / min and a temperature of 250°C for 8 minutes. After the reaction, an antibacterial polypropylene melt was obtained, and the antibacterial polypropylene melt was melt-spun by a melt-blown spinning machine to obtain a 30 g / m 2 Meltblown layer material;
[0115] The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 260°C, the melt pump speed is 220r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 24cm and a temperature of 10°C, and then charged for 1min at a voltage of 50kV and a spacing of 35cm.
[0116] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0117] Dimethylaminoethyl methacrylate was mixed and dissolved with ethanol and isopropanol, and a modified zinc oxide / montmorillonite composite material and potassium iodide were added, wherein the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide was 5:15:30:5:0.3. The preparation of the modified zinc oxide / montmorillonite composite material was the same as that in Example 1, and the reaction was carried out at 60° C. for 8 h. After the reaction was completed, the mixture was filtered, and the filter cake was taken, and ethanol in an amount of 8 times the mass of the filter cake was added for washing, and the mixture was dried at 60° C. for 20 h to obtain a quaternized zinc oxide / montmorillonite composite material.
[0118] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0119] Step (1), mixing the polyester fiber with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:50, pre-treating at 80° C. for 20 min, taking out after the treatment, adding water to wash until neutral, and drying at 60° C. for 18 h to obtain the pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, the yarn count is 40S in British standard, spinning cotton fiber into yarn as weft yarn, the yarn count is 40S in British standard, weaving, and obtaining a yarn with a gram weight of 130 g / m 2 Polyester / cotton fabric;
[0120] Step (2), mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate, and water in a mass ratio of 20:5:2:3:1:1000, the preparation of the alkenyl polyester / cotton fabric is the same as that in Example 1, dipping at 85°C for 0.5h, double dipping and double rolling, with a rolling rate of 82%, and after the dipping is completed, baking at 160°C for 2min to obtain a modified polyester / cotton fabric;
[0121] Wherein, alkenyl hydantoin is prepared by the following steps:
[0122] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, and water were mixed and dissolved, and reacted at 50°C for 20 minutes. After the reaction, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was added. The mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was 9:6:10:180:8.5. The reaction was continued at 50°C for 24 hours. After the reaction was completed, the solvent water was removed by rotary evaporation at 80°C to obtain a reaction product. Ethanol 5 times the mass of the reaction product was added, stirred for 1 hour, filtered, and the filter cake was taken and dried at 80°C for 12 hours to obtain modified hydantoin.
[0123] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol were mixed in a mass ratio of 35:17:50:70, reacted at 70°C for 18 hours, and after the reaction, the solvent water and ethanol were removed by rotary evaporation at 70°C, and dried at 60°C for 12 hours to obtain allylated hydantoin;
[0124] Step (3), immersing the modified polyester / cotton fabric in a 10wt% sodium hypochlorite aqueous solution with a bath ratio of 50:1, chlorinating at room temperature for 2h, taking out after the chlorination, washing with water, and drying at 50°C for 10h to obtain a surface fabric and an inner fabric respectively;
[0125] Step 3: laminate the surface fabric, meltblown layer material, and inner layer fabric in turn, align the layers, use polyester filament sewing thread as sewing thread, and sew the surface fabric, meltblown layer material, and inner layer fabric through a multi-layer fabric quilting machine to obtain a sun-proof and antibacterial layered composite fabric.
[0126] Comparative Example 1
[0127] This comparative example discloses a method for preparing a fabric, comprising the following steps:
[0128] Step (1), mixing the polyester fiber with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:40, pre-treating at 70° C. for 30 min, taking out after the treatment, adding water to wash until neutral, and drying at 50° C. for 20 h to obtain the pre-treated polyester fiber; spinning the pre-treated polyester fiber into yarn as warp yarn, the yarn count is 30S in British standard, spinning cotton fiber into yarn as weft yarn, the yarn count is 30S in British standard, weaving, and obtaining a yarn with a gram weight of 120 g / m 2 Polyester / cotton fabric;
[0129] Step (2), mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate, and water in a mass ratio of 20:4:1.8:2:0.8:1000, the preparation of the alkenyl polyester / cotton fabric is the same as that in Example 1, dipping at 75°C for 1h, double dipping and double rolling, with a rolling rate of 78%, and after the dipping is completed, baking at 150°C for 3min to obtain a modified polyester / cotton fabric;
[0130] Wherein, alkenyl hydantoin is prepared by the following steps:
[0131] L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, and water were mixed and dissolved, and reacted at 40°C for 40 minutes. After the reaction, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was added. The mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was 8.7:5.8:9.6:150:8.2. The reaction was continued at 40°C for 26 hours. After the reaction was completed, the solvent water was removed by rotary evaporation at 70°C to obtain a reaction product. Ethanol 4 times the mass of the reaction product was added, stirred for 0.5 hours, filtered, and the filter cake was taken and dried at 70°C for 16 hours to obtain modified hydantoin.
[0132] 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol were mixed in a mass ratio of 34:16.5:40:60, reacted at 60°C for 22h, and after the reaction, the solvent water and ethanol were removed by rotary evaporation at 70°C, and dried at 50°C for 14h to obtain allylated hydantoin;
[0133] Step (3), immersing the modified polyester / cotton fabric in a 10wt% sodium hypochlorite aqueous solution with a bath ratio of 40:1, chlorinating at room temperature for 1 hour, taking out after the chlorination, washing with water, and drying at 40°C for 12 hours to obtain a surface layer fabric and an inner layer fabric, respectively;
[0134] The surface fabric and the inner fabric are sequentially laminated and aligned, and polyester filament sewing thread is used as the sewing thread. The surface fabric and the inner fabric are sewn together by a multi-layer fabric quilting machine to obtain the fabric.
[0135] Comparative Example 2
[0136] This comparative example discloses a method for preparing a fabric, comprising the following steps:
[0137] Step 1, preparing meltblown layer material;
[0138] The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide were mixed in a mass ratio of 100:3:0.4, and melt-reacted for 10 minutes in a twin-screw extruder at a screw speed of 250 r / min and a temperature of 230°C. After the reaction, an antibacterial polypropylene melt was obtained, and the antibacterial polypropylene melt was melt-spun by a melt-blown spinning machine to obtain a 20 g / m 2 Meltblown layer material;
[0139] The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 240°C, the melt pump speed is 200r / min, and the melt is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 20cm and a temperature of 5°C, and then charged for 2min at a voltage of 45kV and a spacing of 30cm;
[0140] The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps:
[0141] Dimethylaminoethyl methacrylate was mixed and dissolved with ethanol and isopropanol, and a modified zinc oxide / montmorillonite composite material and potassium iodide were added, wherein the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide was 4.7:10:20:5:0.2. The preparation of the modified zinc oxide / montmorillonite composite material was the same as that in Example 1, and the reaction was carried out at 50° C. for 10 h. After the reaction was completed, the mixture was filtered, and the filter cake was taken, and ethanol 5 times the mass of the filter cake was added for washing, and the mixture was dried at 50° C. for 24 h to obtain a quaternary ammonium zinc oxide / montmorillonite composite material.
[0142] Step 2: preparing the surface layer fabric and the inner layer fabric;
[0143] The polyester fiber was mixed with 150 g / L sodium hydroxide aqueous solution at a mass ratio of 1:40, pretreated at 70°C for 30 minutes, taken out after the treatment, washed with water until neutral, and dried at 50°C for 20 hours to obtain the pretreated polyester fiber; the pretreated polyester fiber was spun into yarn as warp yarn, the yarn count was 30S in British system, and the cotton fiber was spun into yarn as weft yarn, the yarn count was 30S in British system, and woven to obtain 120 g / m 2 The surface fabric and lining fabric;
[0144] Step 3: sequentially laminate the surface fabric, meltblown layer material, and inner layer fabric, align the layers, use polyester filament sewing thread as sewing thread, and sew the surface fabric, meltblown layer material, and inner layer fabric through a multi-layer fabric quilting machine to obtain the fabric.
[0145] In the above embodiments and comparative examples: polypropylene melt-blown resin comes from China National Chemical Corporation, with a melt flow index of 1500 g / min; montmorillonite comes from Shanghai McLean Biochemical Technology Co., Ltd., with a product name of calcium-based montmorillonite K-10, product number M813515, CAS number: 1318-93-0; zinc acetate comes from Shanghai Aladdin Biochemical Technology Co., Ltd., with a product name of anhydrous zinc acetate, CAS number: 557-34-6, and dimethylaminoethyl methacrylate comes from Alfa Aesar, CAS No.: 2867-47-2; Allyl-β-cyclodextrin is from Shandong Binzhou Zhiyuan Biological Co., Ltd., product name allyl-β-cyclodextrin allyl-CD; 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole is from Shanghai Aladdin Biochemical Technology Co., Ltd., product number H157097, CAS No.: 96478-09-0; L-arginine is from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 74-79 -3; 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione was from Shanghai Kewei Chemical Company, CAS number: 112651-38-4; 4-allyloxybenzaldehyde was from Shanghai McLean Biochemical Technology Co., Ltd., product number A916110, CAS number: 40663-68-1; the polyester fiber was polyester staple fiber with a fineness of 1.5D and a fiber length of 38mm; the cotton fiber was long-staple cotton with a fiber length of 38-39mm; the yarn count of the polyester sewing thread was British count 20S.
[0146] Test example
[0147] The fabrics prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests, and the specific test results are shown in Table 1; the fabrics prepared in Examples 1-5 and Comparative Examples 1-2 were respectively prepared into mask samples, recorded as Samples 1-8, and the performance tests were performed on Samples 1-8, and the specific test results are shown in Table 2:
[0148] Table 1
[0149]
[0150] Table 2
[0151]
[0152] The detection of each index in Table 1 and Table 2 is based on the following standards: the antibacterial rate is determined by referring to GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method", and Escherichia coli is selected as the bacteria; the anti-ultraviolet performance is represented by UPF and UVA, and is determined by referring to GB / T18830-2009 "Evaluation of Ultraviolet Protection Performance of Textiles"; the inhalation resistance, exhalation resistance and filtration efficiency are all determined by referring to GB / T32610-2016 "Technical Specifications for Daily Protective Masks", and the filtration efficiency test is graded as Level 2.
[0153] It can be seen from the test results in Table 1 and Table 2 that the fabric prepared by the present invention has excellent anti-ultraviolet and antibacterial properties and good filtering performance, and can be used as a raw material to prepare masks.
[0154] The present invention prepares a quaternized zinc oxide / montmorillonite composite material with antibacterial and anti-ultraviolet properties, grafts it onto a polypropylene molecular chain, improves the compatibility between the filler and the matrix, and the prepared melt-blown layer material not only has anti-ultraviolet and good filtering properties, but also has excellent antibacterial properties;
[0155] The invention soaks alkenyl polyester / cotton fabric in a finishing solution containing alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole and an initiator, so that each functional component is grafted and fixed on the surface of the polyester / cotton fabric through a free radical reaction, and the obtained modified polyester / cotton fabric is chlorinated to obtain a surface layer fabric and an inner layer fabric; wherein the alkenyl hydantoin is used as a precursor structure of a halamine antibacterial agent, and forms a nitrogen-halogen bond after chlorination, and has broad-spectrum bactericidal property, stability, regeneration of antibacterial performance and safety. It has many advantages such as fullness, and can cooperate with L-arginine and Schiff base bond with antibacterial properties in the molecular structure of alkenyl hydantoin to effectively improve the antibacterial properties of fabrics; cyclodextrin and its derivatives have a special molecular structure with hydrophilicity on the outside and hydrophobicity on the inside. Fixing them on the fabric can not only further improve the air filtration efficiency of the fabric, but also improve the moisture absorption performance of the fabric; 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole as a benzotriazole ultraviolet absorption monomer can improve the anti-ultraviolet performance of the fabric;
[0156] In Comparative Example 1, no meltblown layer material is added, and the improvement effect of the polypropylene meltblown nonwoven material on the filtration performance is lacking, so the filtration performance of Comparative Example 1 is not as good as that of the embodiment. At the same time, since the meltblown layer material is added with quaternized zinc oxide / montmorillonite composite material, it also has anti-ultraviolet and antibacterial properties, so the anti-ultraviolet and antibacterial properties of Comparative Example 1 are lower than those of the embodiment;
[0157] In Comparative Example 2, the surface fabric and the inner fabric were not surface modified, and were not impregnated with the finishing liquid containing alkenyl hydantoin, allyl-β-cyclodextrin, and 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, so the antibacterial and anti-ultraviolet properties of the fabric were reduced, so the anti-ultraviolet and antibacterial properties of Comparative Example 2 were lower than those of the embodiment.
[0158] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a sun-proof and antibacterial layered composite fabric, characterized in that: The following steps are involved: Step 1, preparing meltblown layer material; The polypropylene melt-blown resin, the quaternized zinc oxide / montmorillonite composite material and the dicumyl peroxide are mixed and melt-reacted to obtain an antibacterial polypropylene melt after the reaction is completed. The antibacterial polypropylene melt is melt-spun by a melt-blown spinning machine to obtain a melt-blown layer material. The quaternized zinc oxide / montmorillonite composite material is prepared by the following steps: Step (1), mixing montmorillonite, hexadecyltrimethylammonium bromide and water, reacting, adding a regulator to adjust the pH value after the reaction, adding zinc acetate and tetraethoxysilane, and continuing the reaction, and after the reaction, centrifuging, filtering, washing, drying, grinding and sieving, and calcining to obtain a zinc oxide / montmorillonite composite material; Step (2), ultrasonically dispersing the zinc oxide / montmorillonite composite material and toluene, adding water, and dropwise adding 3-chloropropyltrimethoxysilane. After the dropwise addition is completed, reacting, filtering, washing, and drying after the reaction is completed to obtain a modified zinc oxide / montmorillonite composite material; The dimethylaminoethyl methacrylate is mixed with ethanol and isopropanol to dissolve, and the modified zinc oxide / montmorillonite composite material and potassium iodide are added to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a quaternized zinc oxide / montmorillonite composite material. Step 2: preparing the surface layer fabric and the inner layer fabric; Step (1), mixing alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate and water, impregnating, and after the impregnation, baking to obtain a modified polyester / cotton fabric; Step (2), immersing the modified polyester / cotton fabric in a sodium hypochlorite aqueous solution for chlorination, taking it out after the chlorination is completed, washing it with water, and drying it to obtain a surface layer fabric and an inner layer fabric respectively; Step 3: Compound the surface layer fabric, melt-blown layer material and inner layer fabric in sequence to obtain a sun-proof and antibacterial layered composite fabric.
2. The method for preparing a sun-proof and antibacterial layered composite fabric according to claim 1, characterized in that: In the step 1, the mass ratio of polypropylene melt-blown resin, quaternized zinc oxide / montmorillonite composite material, and dicumyl peroxide is 100:3-5:0.4-0.5; the melting reaction conditions are: in a twin-screw extruder, the screw speed is 250-300r / min, and the temperature is 230-250°C for melting reaction for 8-10min; the gram weight of the melt-blown layer material is 20-30g / m 2 ; The operation of melt spinning is as follows: the antibacterial polypropylene melt is pumped into the spinneret at a temperature of 240-260°C, the melt pump speed is 200-220r / min, and it is stretched by hot air at an air flow pressure of 2.1MPa and a temperature of 300°C, and then cooled and bonded into a web at a receiving distance of 20-24cm and a temperature of 5-10°C, and then charged for 1-2min at a voltage of 45-50kV and a spacing of 30-35cm.
3. The method for preparing a sun-proof and antibacterial layered composite fabric according to claim 1, characterized in that: When preparing the quaternized zinc oxide / montmorillonite composite material in step (1), the mass ratio of montmorillonite, hexadecyltrimethylammonium bromide, water, zinc acetate and tetraethoxysilane is 1:4-4.2:40-50:1.8-2:1.6-1.8; the reaction conditions are: reacting at a temperature of 70-80°C for 12-16 hours; continuing the reaction conditions are: continuing the reaction at a pH value of 8-9 and a temperature of 70-80°C for 2-3 hours; and the calcination conditions are: calcining at a temperature of 550-580°C for 5-6 hours. When preparing the quaternized zinc oxide / montmorillonite composite material in step 1, in step (2), the mass ratio of the zinc oxide / montmorillonite composite material, 3-chloropropyltrimethoxysilane, toluene and water is 5:5.5-6:40-50:5-6, and the dripping time of 3-chloropropyltrimethoxysilane is 10-15 minutes; when preparing the modified zinc oxide / montmorillonite composite material, the reaction conditions are: reacting at room temperature for 8-10 hours; the mass ratio of dimethylaminoethyl methacrylate, ethanol, isopropanol, modified zinc oxide / montmorillonite composite material and potassium iodide is 4.7-5:10-15:20-30:5:0.2-0.3; when preparing the quaternized zinc oxide / montmorillonite composite material, the reaction conditions are: reacting at a temperature of 50-60°C for 8-10 hours.
4. The method for preparing a sun-proof and antibacterial layered composite fabric according to claim 1, characterized in that: In step (1) of step 2, the olefin-based polyester / cotton fabric is prepared by the following steps: The polyester fiber is mixed with a sodium hydroxide aqueous solution for pretreatment, taken out after the treatment, washed to neutrality, and dried to obtain the pretreated polyester fiber; the pretreated polyester fiber is spun into yarn as warp yarn, the cotton fiber is spun into yarn as weft yarn, and weaved to obtain a polyester / cotton fabric; The mass ratio of polyester fiber to sodium hydroxide aqueous solution is 1:40-50, and the sodium hydroxide aqueous solution is 150 g / L sodium hydroxide aqueous solution; the pretreatment conditions are: pretreatment at 70-80°C for 20-30 min; the yarn count of the pretreated polyester fiber is 30-40S in British standard; the yarn count of the cotton fiber is 30-40S in British standard; the weight of the polyester / cotton fabric is 120-130 g / m 2 ; Mixing γ-methacryloxypropyltrimethoxysilane, ethanol aqueous solution, and pretreated polyester / cotton fabric, reacting, taking out after the reaction, washing, continuing the reaction, and drying after the reaction to obtain olefin-based polyester / cotton fabric; Among them, the mass ratio of γ-methacryloxypropyltrimethoxysilane, 80wt% ethanol aqueous solution, and pretreated polyester / cotton fabric is 5-6:100:2, and the ethanol aqueous solution is 80wt% ethanol aqueous solution; the reaction conditions are: react at a temperature of 30-40°C for 3-4h; the continued reaction conditions are: continue to react at a temperature of 100-120°C in a drying oven for 1-2h.
5. The method for preparing a sun-proof and antibacterial layered composite fabric according to claim 1, characterized in that: In step (1) of step 2, alkenyl hydantoin is prepared by the following steps: L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride and water are mixed and dissolved, and reacted. After the reaction is completed, 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione is added, and the reaction is continued. After the reaction is completed, the solvent water is removed by rotary evaporation to obtain a reaction product, and ethanol is added, stirred, filtered, and dried to obtain modified hydantoin; 4-allyloxybenzaldehyde, modified hydantoin, water and ethanol are mixed and reacted. After the reaction is completed, the solvent water and ethanol are removed by rotary evaporation, and dried to obtain alkenyl hydantoin; Among them, the mass ratio of L-arginine, N-hydroxysuccinimide, carbodiimide hydrochloride, water, and 3-(2-aminoethyl)-5,5-dimethylimidazolidine-2,4-dione is 8.7-9:5.8-6:9.6-10:150-180:8.2-8.5; when preparing modified hydantoin, the reaction conditions are: react at 40-50°C for 20-40 minutes, and the continued reaction conditions are: continue to react at 40-50°C for 24-26 hours; the mass ratio of 4-allyloxybenzaldehyde, modified hydantoin, water, and ethanol is 34-35:16.5-17:40-50:60-70; when preparing alkenyl hydantoin, the reaction conditions are: react at 60-70°C for 18-22 hours.
6. The method for preparing a sun-proof and antibacterial layered composite fabric according to claim 1, characterized in that: In step (1) of step 2, the mass ratio of alkenyl polyester / cotton fabric, alkenyl hydantoin, allyl-β-cyclodextrin, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, potassium persulfate and water is 20:4-5:1.8-2:2-3:0.8-1:1000; the dipping operation includes: dipping at a temperature of 75-85°C for 0.5-1h, double dipping and double rolling, and the rolling rate is 78-82%.
7. The method for preparing a sun-proof and antibacterial layered composite fabric according to claim 1, characterized in that: In step (2) of step 2, the bath ratio of the modified polyester / cotton fabric to the sodium hypochlorite aqueous solution is 40-50:1, and the sodium hypochlorite aqueous solution is a 10 wt % sodium hypochlorite aqueous solution; the chlorination conditions are: chlorination at room temperature for 1-2 hours.
8. A sun-proof and antibacterial layered composite fabric prepared based on the method for preparing the sun-proof and antibacterial layered composite fabric as claimed in any one of claims 1 to 7.
9. A mask prepared based on the sun-proof and antibacterial layered composite fabric according to claim 8.
Citation Information
Patent Citations
Antibacterial health-caring, anti-ultraviolet environment-friendly composite fabric and preparation method thereof
CN109291563A
Beta-cyclodextrin containing halogen amine antimicrobial agent copolymer as well as preparation method and application of copolymer
CN103554367A
Antibacterial polypropylene fiber and preparation method
CN109913968A